Modulação vetorial otimizada para o conversor packed U-cell - Schuetz, Dimas Alã (2020)
This master’s dissertation proposes space vector modulation strategies for the Five-Levels Packed U-Cell converter with optimization on the commutation number and balance of the floating capacitors by use a cost function. Initially, the converter three-phase topology and their commutation states are presented, from which the redundant states are highlighted. In sequence, some concepts of the main modulation strategies for multilevel converters are present and the discontinuous modulation strategies features are introduced. Based on the discontinuous modulation features, it is proposed the definition of the reference vector for the space vector modulation so that, when mapped to the 3D space vector diagram, it remains clamped to one face for a certain time period. As a result, it is possible to decompose the 3D space vector diagram in 2D planes, make the search of the reference nearest vectors easier. Furthermore, the space vector diagram representation in the abc coordinates do not present redundancies in the converter phase-to-phase voltages space, reducing the algorithm computational effort. In this way, switching sequence definition ways are proposed in order to minimize the number of phase voltages transitions between two adjacent vectors, and result in output voltages with half-wave symmetry. Starting from the Packed U-Cell converter redundancies, the distance about the last implemented vector is calculated as well as the error between the medium current reference for balance the capacitor voltages, given by PI controllers, and the prediction current that flows across these capacitors for each redundant state, remembering the Model Predictive Control technique. By the proposed cost function, composed by the above mentioned parcels, it is selected the redundancy that presents the least cost. The proposed modulation strategies performance is analyzed by simulation and experimental results, considering the connection cases of the Packed U-Cell converter with a resistive-inductive load. Based on the obtained results, comparative analyses with previous proposed modulation strategies for this converter are presented, showing advantages in terms of commutations number and better performance of harmonic distortion values in the output voltages.